Does Human Capital Matter for Indonesia's Economic Growth? - Vita Kartika Sari; Dwi Prasetyani (Jurnal Ekonomi Pembangunan)
This study investigates the impact of human capital in the context of health and education on Indonesia's economic growth, which includes physical capital investment and trade openness as control variables. Using time series data from 1981 to 2022 and employing econometric techniques by applying the ARDL model. The findings reveal that education, investment, and trade openness have a positive and statistically significant impact on Indonesia's economic growth. Surprisingly, life expectancy has a negative and significant impact on Indonesia's economic growth. This unexpected result warrants further investigation to identify potential confounding factors or data limitations. Despite this finding, the study emphasizes the crucial role of health in human capital and long-run economic prosperity. Among the policy suggestions are enhancing nutrition, guaranteeing access to high-quality healthcare, and maximizing health transformation through the development of public health services. Concurrently, investments in education, particularly in improving quality, accessibility, and alignment with labor market demands, are essential. These findings underscore the need for a comprehensive approach to economic development that prioritizes human capital development while addressing the complexities of health-growth relationships.